The failure of community-based health insurance schemes in Tanzania: opening the black box of the implementation process - Ramadhani Kigume; Stephen Maluka (BMC, 2021)
Abstract Background Globally, there is increased advocacy for community-based health insurance (CBHI) schemes. Like other low and middle-income countries (LMICs), Tanzania officially established the Community Health Fund (CHF) in 2001 for rural areas; and Tiba Kwa Kadi (TIKA) for urban population since 2009. This study investigated the implementation of TIKA scheme in urban districts of Tanzania. Methods A descriptive qualitative case study was conducted in four urban districts in Tanzania in 2019. Data were collected using semi-structured interviews, focus group discussions and review of documents. A thematic approach was used to analyse the data. Results While TIKA scheme was important in increasing access to health services for the poor and other disadvantaged groups, it faced many challenges which hindered its performance. The challenges included frequent stock-out of drugs and medical supplies, which frustrated TIKA members and hence contributed to non-renewal of membership. In addition, the scheme was affected by poor collections and management of the revenue collected from TIKA members, limited benefit packages and low awareness of the community. Conclusions Similar to rural-based Community Health Fund, the TIKA scheme faced structural and operational challenges which subsequently resulted into low uptake of the schemes. In order to achieve universal health coverage, the government should consider integrating or merging Community-Based Health Insurance schemes into a single national pool with decentralised arms to win national support while also maintaining local accountability.